Analisis Kondisi Kran Kapal, Jumlah Trucking dan Waktu Kerja di Gudang Penerima terhadap Tingginya Berthing Time Kapal - Abdul Muis; Kemal Heryandri; Wahyono Bimarso; Euis Saribanon; Silvia Dewi Kumalasari (Dinasti Review, 2024)
The Influence of Ship Crane Conditions, Number of Trucking and Number of Trucking on the High Berthing Time of Ships. is a scientific article on library research within the scope of the field of science. The aim of this article is to build a hypothesis of influence between variables that will be used in further research. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. The research method using the research library comes from e-books and open access e-journals. Qualitative descriptive analysis. The results of this article: 1) The influence of the condition of the ship's cranes on the high berthing time of the ship; 2) The amount of trucking influences the ship's berthing time; and 3) Working Time in the Receiving Warehouse influences the High Berthing Time of the Ship.